Data Communication Stability Test a Data Acquisition System (DAQ) for Inpatient Rooms - Utami, Sentagi Sesotya; Setyonugroho, Winny; Permana, Iman; Lestari, Tri; Taher, Muhammad Dian Saputra; Khanif, Akhmad; Utomo, Gilang Ari Widodo (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
In inpatient services, the patient's bed is usually limited by a curtain or partition to maintain patient safety. At the time of data collection, obstacles or obstacles were considered as a result of effectiveness and validation of medical device sensor data. This study aims to explain the results of testing the reliability of Bluetooth and internet on CovWatch hardware and applications. This research is an action research; used comparisons using devices (tools) with different specifications. Testing internet and Bluetooth connectivity from the CovWatch unit and applications installed on the Samsung A01, Redmi Note 10 and Oppo A57 devices, the results were mixed. Measurement of the range of connectivity is carried out using a barrier (Selected Semi PVC, Multiplex, Kalsiboard) and without a barrier. The results of this experiment show that the CovWatch Hardware and Samsung A01 are considered the best at obtaining vital sign data, while the Redmi Note 10 and OPPO A57 are not good because some data cannot be obtained so they do not appear on the monitor unit. This test identifies obstructions and optimal distances that can be used to provide data quickly, adopting innovative, flexible and integrated care delivery models to ensure optimal continuity and access.